Patterns of Retinal Nerve Fiber Layer Loss in Different Subtypes of Open Angle Glaucoma Using Spectral Domain Optical Coherence Tomography. Issue 10 (October 2016) - Baniasadi, Neda; Paschalis, Eleftherios I.; Haghzadeh, Mahdi; Ojha, Pallavi; Elze, Tobias; Mahd, Mufeed; Chen, Teresa C.
Abstract : Purpose of the Study: The purpose of the study was to determine whether there are different patterns of retinal nerve fiber layer (RNFL) thinning as measured by spectral domain optical coherence tomography (SD-OCT) for 4 subtypes of open angle glaucoma (OAG): primary OAG (POAG), normal tension glaucoma (NTG), pseudoexfoliation glaucoma (PXG), and pigmentary glaucoma (PDG) and to compare them with normal controls. Materials and Methods: SD-OCT RNFL thickness values were measured for 4 quadrants and for 4 sectors (ie, superior-nasal, superior-temporal, inferior-nasal, and inferior-temporal). Differences in RNFL thickness values between groups were analyzed using analysis of variance. Paired t tests were used for quadrant comparisons. Results: Two hundred eighty-five participants (102 POAG patients, 33 with NTG, 48 with PXG, 13 with PDG, and 89 normal patients) were included in this study. All 4 subtypes of OAG showed significant RNFL thinning in the superior, inferior, and nasal quadrants as well as the superior-temporal and inferior-temporal sectors (all P -values <0.0001) compared with normals. POAG and NTG patients had greater RNFL thinning inferiorly and inferior-temporally than superiorly ( P -values: 0.002 to 0.018 and 0.006, respectively) compared with PXG patients. In contrast, PDG patients had greater RNFL thinning superiorly and superior-nasally than inferiorly compared with other OAG subtypes (ie, POAG, NTG, PXG groups, with P -values: 0.009, 0.003, 0.009, respectively). Of the 4 OAG subtypes, PXG patients exhibited the greatest degree of inter-eye RNFL asymmetry. Conclusions: This study suggests that SD-OCT may be able to detect significant differences in patterns of RNFL thinning for different subtypes of OAG.